B-acute Lymphoblastic Leukemia With Hypereosinophilia Associated With Severe Cardiac Complications: A Clinical Case. Issue 1 (January 2021) - Lahfafa, Anissa; de Ville de Goyet, Maëlle; Boulanger, Cécile; Defour, Jean-Philippe; Detaille, Thierry; Van Damme, An; Brichard, Bénédicte
Abstract : Hypereosinophilia (HE) is rare but often secondary to a nonhematologic disease such as allergic disorders and parasitic infections. HE can also be associated with hematologic malignancies and be the result of a clonal proliferation or reactive to another hematologic condition. Association of HE with acute lymphoblastic leukemia (ALL) is rare in children. We reported a case of a teenager presented with HE secondary to B-ALL who experienced severe cardiac complications with severe absolute eosinophil count. We compared his clinical evolution with other published cases and we reported 2 mutations linked to B-ALL never described before in this context.